Profiles of children with Down syndrome who meet screening criteria for autism spectrum disorder (ASD): a comparison with children diagnosed with ASD attending specialist schools. Issue 1 (21st November 2016) - Warner, G.; Howlin, P.; Salomone, E.; Moss, J.; Charman, T.
Abstract: Background: Recent research suggests that around 16% to 18% of children with Down syndrome (DS) also meet diagnostic criteria for autism spectrum disorder (ASD). However, there are indications that profiles of autism symptoms in this group may vary from those typically described in children with ASD. Method: Rates of autism symptoms and emotional and behavioural problems among children with DS who screened positive for ASD on the Social Communication Questionnaire (SCQ) (n = 183) were compared with a group of children with clinical diagnoses of ASD (n = 189) attending specialist schools in the UK. Groups were matched for age and approximate language level (use of phrase speech). Results: Profiles of autistic symptoms in the two groups were generally similar, but children with DS meeting ASD cut‐off on the SCQ tended to show fewer problems in reciprocal social interaction than those in the ASD group. They also showed slightly lower rates of emotional and peer‐related problems. The results mostly confirm findings from a previous study in which the original validation sample for the SCQ was used as a comparison group. Conclusion: Findings suggest that children with DS who meet screening criteria for ASD show similar profiles of communication and repetitive behaviours to those typically described in autism. However, they tend to have relatively milder social difficulties. It is important that clinicians are aware of this difference if children with DS and ASD are to be correctly diagnosed and eligible for specialist intervention and education services.